Effects of Trastuzumab on Alternative Splicing in HER2+ BT474 Breast Cancer Cells - Piticaru, Benjamin (University of Waterloo, 2024)
Alternative splicing (AS) is a fundamental process that enhances transcriptomic diversity and protein isoform complexity in eukaryotic cells. Deregulation of AS plays a critical role in various diseases, particularly cancer, where erroneous splicing patterns contribute to oncogenesis, tumor progression, and therapeutic resistance. Human epidermal growth factor receptor (HER)2, overexpressed in more than 20% of breast cancers, has clinical relevance in AS. The humanized monoclonal antibody (mAb) Trastuzumab has been used for decades to fight HER2+ breast cancer with positive results. However, there are many unknowns surrounding the mechanism of this drug and the effects it has on alternative splicing. Next generation long read sequencing technologies like Oxford Nanopore allow researchers to sequence full length transcripts. The ability to sequence long intron/exon spans and repeating regions enables long read sequencing technology to provide new insights into the AS patterns of genes. Identifying AS events is important for understanding changes in function and pathways affected by differing conditions (e.g., drug treatment, diseased cells). Software tools tailored to long read data like Long-read Isoform Quantification and Analysis (LIQA), Full-Length Alternative Isoform Analysis of RNA (FLAIR), FLAME, and Nanosplicer enhance data analysis abilities to detect AS events. They analyze sequencing data by mapping reads to genomes, identifying splice junctions, and clustering AS events. These tools then compare AS events between conditions (e.g., treated vs. untreated cells) to pinpoint significant AS variations. Accurate transcriptome sequencing is vital for research in drug development and diagnostics. The optimization of sequencing methods is an ongoing endeavour that requires continuous development. A chapter of this thesis compares the impact of omitting polyadenylation (poly(A)) enrichment in Oxford Nanopore Technologies (ONT)’s direct complementary deoxyribonucleic acid (cDNA) sequencing protocol to improve library prep efficiency and sequencing accuracy. Analysis indicated that excluding poly(A) selection does not negatively affect sequencing metrics but enhances read length and enables the sequencing of histone messenger ribonucleic acid (mRNA). Further, significant differences in poly(A) tail lengths between selected and unselected samples were found, suggesting a bias against shorter tails with enrichment. Gene composition and unique gene identification remain consistent across conditions. These findings support the potential advantages of omitting poly(A) enrichment in transcriptome sequencing while advocating for further validation. With optimized methods, the impact of Trastuzumab on AS profiles in BT474 and SKBR3 cell lines was tested. Using ONT long-read sequencing, significant AS events were identified in response to Trastuzumab treatment. The findings reveal differential isoform expression in genes involved in cellular signaling, RNA processing, and stress response pathways. Notably, nuclear paraspeckle assembly transcript 1 (NEAT1) and pre-mRNA processing factor 38B (PRPF38B) exhibited distinct AS patterns across multiple cell lines, suggesting HER2-mediated regulatory mechanisms. This study underscores the utility of ONT sequencing and high throughput data processing as an effective and efficient means for explaining complex AS landscapes affected by therapeutic treatments.
Keywords: HER2; transcriptomics; nanopore; RNA sequencing; alternative splicing; mRNA; molecular biology; cellular biology; cancer biology; breast cancer; bioinformatics; long read sequencing; LIQA; Nextflow; Oxford Nanopore Technologies; poly(A) enrichment; library preparation methods; RNA extractions; cDNA synthesis; Trastuzumab; Herceptin; monoclonal antibody